CULTURAL CODE IN THE “DON” NOMINATION AND ITS USE IN LITERATURE AND JOURNALISM (Proceedings of Southern Federal University. Philology, 2022)
DOI 10.18522/1995-0640-2022-3-206-212Research topics related to the reflection of ethnic processes and phenomena in the media is one of the most relevant in today’s multinational community. The most effective way to involve the audience in the current dialogue is to use the cultural code, which is the key to understanding the unique features of the culture that has come down to different peoples from their ancestors. The Don is one of the toponyms most used in the media, combining the potamonym – the name of the river and the horonim – the name of the territory. The new nomination of the word Don loses some of its former meanings, acquiring implicit uncertainty and acquiring a wide range of extralinguistic information that represents its connection with cultural, historical, ethnic, estate, religious and other specific traditions, and the characteristics of the Don Cossacks and other inhabitants of the region in the context certain time. In this sense, we are dealing with a cultural code correlated with the historical memory of the bearers of this code. Cultural codes associated with the historical memory of different peoples open up new paradigms of scientific research in cultural studies, history, futurology, sociology, linguistics and other fields of knowledge, aimed at studying the deep layers of memory inherited from their ancestors, and the processes of habitation of this memory, expressed, sometimes unconsciously, in the mass consciousness, in culture, art and mass media.Key words: ethnos, Don, toponym, cultural code, historical memory